A numerical approach to characterize the viscoelastic behaviour of fibre beds and to evaluate the influence of strain deviations on viscoelastic parameter extraction. (April 2021) - Werlen, Vincent; Rytka, Christian; Michaud, Véronique
Abstract: The development of a robust material model able to accurately describe fibre bed compaction at different strain and strain rates is highly desirable because it is essential for the simulation of many composite manufacturing processes. In this study, we investigate the validity of an analytical viscoelastic model approach for different fabrics and at a wide range of strains, both in dry and wet conditions. We propose a numerical approach to determine the parameters of the material model that can overcome simplifications usually met with analytical approaches. We show that a three-branches Maxwell model with strain dependent stiffness and strain-rate dependent dampers can accurately describe the viscoelastic compaction behaviour of fibre beds at different strains and strain speeds, both in dry and wet conditions. We demonstrate that strain deviations have a considerable impact on the viscoelastic parameter extraction and should be taken into account. Highlights: Validation of a three-branches Maxwell model in dry and wet conditions. A numerical approach to determine the parameters of the material model. Strain deviations have a considerable impact on the viscoelastic parameter extraction.